2022
DOI: 10.1021/acsinfecdis.1c00536
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Antimicrobial Peptoids Impacts Their Biological Effects on ESKAPE Bacterial Pathogens

Abstract: Antimicrobial peptides (AMPs) are promising pharmaceutical candidates for the prevention and treatment of infections caused by multidrug-resistant ESKAPE pathogens, which are responsible for the majority of hospital-acquired infections. Clinical translation of AMPs has been limited, in part by apparent toxicity on systemic dosing and by instability arising from susceptibility to proteolysis. Peptoids (sequence-specific oligo-N-substituted glycines) resist proteolytic digestion and thus are of value as AMP mimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 60 publications
2
89
0
Order By: Relevance
“…Prior studies with the 12mer Peptoid 1 have shown great promise against planktonic S. aureus and biofilm-forming bacteria ( 18 , 21 , 23 , 24 , 27 ). The design of this peptoid was originally inspired by that of magainin-2, an antimicrobial peptide found in Xenopus laevis , and consists of four lysine-like monomers ( N Lys) and eight phenylalanine-like monomers ( N -1-S-phenylethyl, N spe) patterned to give the peptoid helical, water-soluble, and amphipathic properties ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior studies with the 12mer Peptoid 1 have shown great promise against planktonic S. aureus and biofilm-forming bacteria ( 18 , 21 , 23 , 24 , 27 ). The design of this peptoid was originally inspired by that of magainin-2, an antimicrobial peptide found in Xenopus laevis , and consists of four lysine-like monomers ( N Lys) and eight phenylalanine-like monomers ( N -1-S-phenylethyl, N spe) patterned to give the peptoid helical, water-soluble, and amphipathic properties ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…Peptoid 1-C13 4mer is five residues long total, with its amino-terminal peptoid side chain being a 13-carbon-long N -alkyl tail, which has shown good activity against biofilms ( 23 , 24 ). The long alkyl tail of Peptoid 1-C13 4mer promotes its self-assembly into ellipsoidal micelles, rather than helical bundles as for Peptoid 1 ( 18 ). The chemical structures of the peptoids used in this study are depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations